Karakteristik Fisik Sabun Organik Berbasis Minyak Jelantah dan Ekstrak Buah Pinang (Areca cathecu L) Dengan Biosurfaktan Buah Lerak (Sapindus rarak DC) - Agustina, Nur Ariyani; Piska, Finna (Agroprimatech, 2023)
Used cooking oil waste is very dangerous for the environment if it is not used or processed properly. Used cooking oil can be used as a raw material for used cooking oil mixed with areca nut. Areca nut contains substances that are beneficial for skin health such as tannins, alkaloids, and flavonoids. In improving the quality of this organic soap, biosurfactants from lerak fruit can also be added as a mixture of organic soaps. This research aims to develop an organic soap based on used cooking oil and areca nut extract with lerak fruit biosurfactant to improve skin health and reduce negative environmental impacts. The research method used a 2 factorial completely randomized design with factor 1, namely areca nut extract (P) which consisted of 3 levels: 4 mL, 6 mL, and 8 mL. Factor 2 was lerak fruit extract (L) which consisted of 3 levels, namely 35%, 45%, and 55%. The research results obtained that activated charcoal and zeolite are very effective in absorbing impurities contained in used cooking oil. This can be seen from the clear golden yellow color of the used cooking oil that has been purified. In organoleptic testing, it was found to have a dark red color, a characteristic odor and a thick texture. The results showed that the addition of areca nut extract and lerak fruit extract had a very significant effect on the results of variance where P<0.05 for all test parameters. The best treatment was found in P3L3 where 8 mL of areca nut extract and 55% of lerak fruit extract resulted in a pH of 8.89, foam height of 10.4 cm, foam stability of 97%, water content of 34.97%. The results of all treatments show that they have fulfilled SNI 06-4085-1996 which can be used as organic liquid body soap. Keyword: lerak, organic soap, used cooking oil, areca nut, biosurfactant